Chemical Literacy: Performance of First Year Chemistry Students on Chemical Kinetics - Muntholib Muntholib; Suhadi Ibnu; Sri Rahayu; Fauziatul Fajaroh; Sentot Kusairi; Bambang Kuswandi (Indonesian Journal of Chemistry, 2020)
This study aims to (1) develop and validate a multiple choice chemical literacy test instrument (MC-CLTI) on chemical kinetics and (2) conduct a small survey on chemical literacy of first year chemistry students. The development of the instrument involved expert consultation and judgment, validation and two times pilot studies. The first pilot study involved 119 first year chemistry students while the second pilot study involved 197 second year chemistry students. The final form of MC-CLTI consists of 30 valid and reliable items (Cronbach's Alpha coefficient = 0.744). The survey showed that the average score of respondents' chemical literacy was 63.24. This score is in the range of the average scores reported by several previous studies.